Alternative Usage of Raw Material and Fuel in Cement Plants: Case Study - Şeyma Ordu; Ebru Öztürk (Doğal Afetler ve Çevre Dergisi)
Turkish Cement Sector uses industrial and domestic wastes as alternative fuels or raw materials in licensed facilities. Increasing use of alternative fuels and raw materials is very important in terms of eliminating environmental pollution, saving natural material resources and energy. Alternative fuels can generally be gathered under the groups of sewage sludge, waste oil, worn out tires, solvent and paints. As for alternative raw materials, they can be evaluated undermine waste, heat treatment waste, construction waste groups. The aim of this study is to evaluate the use of alternative raw materials and fuels and their environmental benefits. For this purpose, in a cement plant selected as a case study, wastes accepted between 2013 and 2015, pre-acceptance analyzes, quantities of alternative raw materials and fuels used, and their financial impacts are examined. Iron scent, grid, casting sand and phosphogypsum are recycled as an alternative raw material in the cement plant in accordance with quality parameters. The use of alternative raw materials resulted in savings totaling 7.031.998 TL for the plant. As alternative fuel, sewage sludge is used. The financial benefit of sewage sludge usage to the plant is 200.514.450 TL.